Addressing Vaccine Hesitancy in BIPOC Communities — Toward Trustworthiness, Partnership, and Reciprocity - Quinn, Sandra C; Andrasik, Michele P (The New England journal of medicine, 2021)
As Covid vaccines are rolled out, it’s time to shift the focus from a sole emphasis on changing hearts and minds among members of BIPOC communities to ensuring that institutions are trustworthy, transparent, and engaged with communities.